Mapeamento geoambiental do campo de dunas Pirangi-Potengi com ênfase a San Vale e Lagoinha Natal/RN: um instrumento de apoio ao planejamento ambiental - Cruz, Igor Silva (2007)
The city of Natal-RN is constructed on dune areas with wavy relives softly waved and green areas that help to keep a pleasant climate, amongst these is distinguished field Pirangi-Potengi the dune with the areas of San Vale and Lagoinha. These environments are being substituted gradual for property and other workmanships of engineering on behalf of the urban expansion. This study the elaboration of a geoambiental mapping of Field had as objective generality Pirangi-Potengi the Dune with emphasis the San Vale and Lagoinha in Natal-RN. The done mapping had as objective specific to elaborate a vegetation map, a map of registers in cadastre of ambient problems to dunes, a map of flooding susceptibility, a map of vulnerability to the underground water contamination and a map of use and occupation of the ground. Of the carried through analysis, the area in study reveals sufficiently degraded, remaining only few green areas and dunares, as well as, the vulnerable presence of areas of vulnerability in floods and areas the contamination of the water-bearing one. The gotten results allow to affirm that this type of mapping, is of great importance for analysis and evaluation of the environment of the city